2018
DOI: 10.4067/s0718-58392018000100117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of source/sink manipulation on grain zinc accumulation by winter wheat genotypes

Abstract: Agronomy practices aimed at wheat (Triticum aestivum L.) grain Zn biofortification are important to alleviate Zn deficiency in humans, especially for those resource-poor people owing to subsistence on diets dominated by cereal-based foods with low concentrations and bioavailability of Zn. To promote understanding of source-sink flow processes affecting biofortification of wheat with Zn, effects of different source/sink manipulations on grain Zn accumulation by wheat were examined in pot and field at two locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In the current study, foliar Zn and/or sucrose applications did not affect the yield or other agronomic traits of maize in Quzhou and Licheng (Tables 3 and 4), suggesting that the dry-matter accumulation in maize grains is less dependent on exogenous foliar Zn and/or carbohydrate supply, at least under the conditions used in this study. Similar results were previously reported for maize and wheat under pot or field conditions [3,26,27,35,38,50,51]. For Zn, this finding may be attributed to the high Zn concentration in soil and the suitable soil conditions, and thus the good Zn nutritional status of plants.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, foliar Zn and/or sucrose applications did not affect the yield or other agronomic traits of maize in Quzhou and Licheng (Tables 3 and 4), suggesting that the dry-matter accumulation in maize grains is less dependent on exogenous foliar Zn and/or carbohydrate supply, at least under the conditions used in this study. Similar results were previously reported for maize and wheat under pot or field conditions [3,26,27,35,38,50,51]. For Zn, this finding may be attributed to the high Zn concentration in soil and the suitable soil conditions, and thus the good Zn nutritional status of plants.…”
Section: Discussionsupporting
confidence: 88%
“…In 1953, it was reported that the addition of sucrose to urea sprays reduced the injury of maize leaves, perhaps by reducing the rate of urea absorption and increasing the rate of urea translocation within the plant [62]. In our previous studies, foliar application of sucrose + Zn was associated with greater improvements in the concentration, content, and bioavailability of Zn in wheat (a C3 plant) than the spraying of Zn only [3,35]. As mentioned by Zhao et al (2014) [51], the relatively higher effectiveness of sucrose + Zn may be attributed to (1) the longer drying time of the spraying solution;…”
Section: Discussionmentioning
confidence: 89%
“…Previous approaches for investigating the source–sink limitations of crop assimilates for grain growth and dry matter accumulation involve reducing the carbohydrate source from photosynthesis (e.g., through defoliation or spike shading) or reducing the grain sink size (e.g., through 50% spikelet removal) after anthesis (Austin & Edrich, 1975; Chang & Zhu, 2017). These approaches have also been applied to investigate the source–sink relationship of micronutrient accumulation in wheat grains (Xia, Xue, Kong, et al, 2018; Zhang, Zhang, et al, 2012; Zhang, Zhou, Zhang, & Wang, 2008). Zhang et al.…”
Section: Physical Manipulation Of Source/sink By Defoliaton Spike Shmentioning
confidence: 99%
“…Zhang et al. (2008), Zhang, Zhang, et al (2012) and Xia, Xue, Kong, et al (2018) all reported experiments whereby defoliation, spike shading, and spikelet removal were employed to manipulate the source or sink of Zn and dry matter in wheat plants. Their results suggested that the accumulation of Zn and dry matter in grains is restricted by source supply and sink capacity, but the effects of reducing source supply or sink capacity on grain Zn concentrations are inconsistent: (a) Defoliation by removing all the leaf blades from tagged culms decreased the source‐to‐sink ratio, which led to decreases in grain Zn concentrations in the studies of Zhang et al.…”
Section: Physical Manipulation Of Source/sink By Defoliaton Spike Shmentioning
confidence: 99%
See 1 more Smart Citation